2018
DOI: 10.1097/md.0000000000010789
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of coronal-STIR sequence in a routine lumbar spine MR imaging protocol to investigate low back pain

Abstract: Aim of this study is to assess the clinical impact of coronal short tau inversion recovery (STIR)-weighted magnetic resonance (MR) sequence, when acquired in a lumbar spine MR imaging protocol, in detecting significant extraspinal imaging findings in patients with low back pain (LBP).We retrospectively evaluated 931 lumbar spine MR examinations of patients with LBP. Extraspinal MR imaging findings were categorized as: probably related to LBP (Category 1), not related to LBP but with relevant implications on pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moe [recently, Romeo et al [18]] studied the coroSTIR sequence in the assessment of isolated low back pain (without radiculopathy) with less convincing results, detecting ESA in only 3.5% (35/931) of cases. This underlines the relevance of performing coroSTIR when low back pain is associated with radiculopathy, probably even more so for cruralgia pain than for lumbosciatica pain because differential diagnoses are more frequent in routine care (hip conditions sometimes resulting in clinical pictures of pseudo-cruralgia).…”
Section: Discussionmentioning
confidence: 99%
“…Moe [recently, Romeo et al [18]] studied the coroSTIR sequence in the assessment of isolated low back pain (without radiculopathy) with less convincing results, detecting ESA in only 3.5% (35/931) of cases. This underlines the relevance of performing coroSTIR when low back pain is associated with radiculopathy, probably even more so for cruralgia pain than for lumbosciatica pain because differential diagnoses are more frequent in routine care (hip conditions sometimes resulting in clinical pictures of pseudo-cruralgia).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that coronal-STIR imaging may provide an additional diagnosis in 6.8% of patients and should be included in the routine lumbar spine MRI protocol (17). Similarly, other studies evaluating the diagnostic efficacy of the coronal-STIR sequence added to the conventional lumbar MR imaging have reported extraspinal incidental findings including vascular, genitourinary, gastrointestinal, musculoskeletal, and oncological pathologies (18)(19)(20)(21)(22)(23). In these studies, the coronal-STIR sequence was performed for the backbone region.…”
Section: Discussionmentioning
confidence: 99%